SPE Asia Pacific Oil and Gas Conference and Exhibition 2013
DOI: 10.2118/165903-ms
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the Art Low Salinity Waterflooding for Enhanced Oil Recovery

Abstract: Low salinity waterflooding (LSW) is an emerging enhanced oil recovery technique in which the salinity of the injected water is controlled to improve oil recovery vs. conventional, higher salinity waterflooding. Despite significant growing interest in LSW, a consistent mechanistic study has not yet emerged, and the mechanisms behind the LSW process have been debated for the last decade due to the complexity of the crude oil-brine-rock interactions. The intent of this paper is to:• Provide a concise review of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…The oil recovery factor was found to increase by about 20 % of the OOIP in low salinity WAG 1:2 as compared to high salinity WAG 1:2 which are in line with the results obtained by Dang et al (2013). High salinity CO2-WAG flooding experiments, using CC (33 cm long) and 20 % of PV of CO 2 divided into two cycles for different CO2-WAG ratios of 1:1, 2:1, and 1:2 at reservoir pressure of 3,200 psia and 250°F were conducted first.…”
Section: High-and Low-salinity Co2-wag Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…The oil recovery factor was found to increase by about 20 % of the OOIP in low salinity WAG 1:2 as compared to high salinity WAG 1:2 which are in line with the results obtained by Dang et al (2013). High salinity CO2-WAG flooding experiments, using CC (33 cm long) and 20 % of PV of CO 2 divided into two cycles for different CO2-WAG ratios of 1:1, 2:1, and 1:2 at reservoir pressure of 3,200 psia and 250°F were conducted first.…”
Section: High-and Low-salinity Co2-wag Performancesupporting
confidence: 90%
“…On the other hand, the secondary recovery of water flooding decreases with the increase of injection brine salinity in the experiments with Cottonwood Creek crude oil. Dang et al (2013) conducted a reservoir simulation on LSW CO 2 four cycles WAG 1:1 and reported a 9 % increase of the OOIP recovery by LSW over high salinity water. To our knowledge very limited work has been reported in the literature that covers the influence of injection brine salinity on CO 2 WAG process and additional work is needed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally found that the low salinity brine has a significant effect on the shape and the end points of the relative permeability curves (Webb et al, 2004;Kulkarni and Rao, 2005;Rivet, 2009;Fjelde et al, 2012), resulting in a lower water relative permeability and higher oil relative permeability. The mechanisms of wettability alteration due to ion exchange and geochemical reactions have been successfully implemented in a compositional simulator for modeling of LSW (Dang et al, 2013b). Excellent agreements between simulation results and important measurements from coreflood experiments and pilot observations were obtained with this modeling approach (Dang et al, 2013a).…”
Section: Introductionmentioning
confidence: 86%
“…Several mechanisms have been proposed during the last two decades including fines migration, wettability alteration, multi-component ionic exchange (MIE), saponification, pH modification, and electrical double layer effects. Dang et al (2013b) provided a critical review and discussion of these mechanisms. Among the proposed hypotheses, wettability alteration towards increased water wetness during LSW is the widely accepted cause for enhanced oil recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation